2018
DOI: 10.1073/pnas.1811957115
|View full text |Cite
|
Sign up to set email alerts
|

Eurasian river spring flood observations support net Arctic Ocean mercury export to the atmosphere and Atlantic Ocean

Abstract: Midlatitude anthropogenic mercury (Hg) emissions and discharge reach the Arctic Ocean (AO) by atmospheric and oceanic transport. Recent studies suggest that Arctic river Hg inputs have been a potentially overlooked source of Hg to the AO. Observations on Hg in Eurasian rivers, which represent 80% of freshwater inputs to the AO, are quasi-inexistent, however, putting firm understanding of the Arctic Hg cycle on hold. Here, we present comprehensive seasonal observations on dissolved Hg (DHg) and particulate Hg (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
101
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 35 publications
8
101
1
Order By: Relevance
“…With an ongoing warming and greening trend associated with climate change, an amplification of the Arctic tundra Hg(0) vegetation pump can be expected. Contrarily, higher soil temperatures, leading to permafrost thaw and degradation and development of thermokarsts, increase the risk of the re-mobilisation of large amounts of Hg that is currently stored in Arctic tundra soils (St. Pierre et al, 2018;Olson et al, 2018;Schuster et al, 2018). The net effect of these complex alterations in Arctic Hg cycling driven by climate change is currently poorly understood and the risk needs to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…With an ongoing warming and greening trend associated with climate change, an amplification of the Arctic tundra Hg(0) vegetation pump can be expected. Contrarily, higher soil temperatures, leading to permafrost thaw and degradation and development of thermokarsts, increase the risk of the re-mobilisation of large amounts of Hg that is currently stored in Arctic tundra soils (St. Pierre et al, 2018;Olson et al, 2018;Schuster et al, 2018). The net effect of these complex alterations in Arctic Hg cycling driven by climate change is currently poorly understood and the risk needs to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Tundra soils play a central role in the Arctic Hg cycling by storing atmospheric Hg deposition from where it can be mobilized and transported to the Arctic Ocean (Obrist et al, 2017;Sonke and Heimburger, 2012;Sonke et al, 2018). Over millennia, 40…”
Section: Introductionmentioning
confidence: 99%
“…Soil core analyses in Alaska indicate that large amounts of carbon and Hg have accumulated since the last glacial maximum, and two upscaling approaches to Hg stocks in pan-Arctic permafrost soils resulted in differing estimates of 184 Gg and 755 Gg for the upper 1 m (Schuster et al, 2018;Olson et al, 2018). Despite the overall net atmospheric Hg deposition to soils, research has found that Arctic rivers export 44 Mg y -1 of soil Hg, bound to particulate and dissolved organic matter, to the Arctic Ocean (Fisher et al, 2012;Dastoor et al, 2014;Zhang et al, 2015;Sonke et al, 2018). Together with coastal erosion of soils (30 Mg y -1 ), river Hg inputs constitute a terrestrial Hg flux of 74 Mg y -1 to the Arctic Ocean that is of similar magnitude to gross atmospheric deposition over the Arctic Ocean (80 Mg y -1 , Sonke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the overall net atmospheric Hg deposition to soils, research has found that Arctic rivers export 44 Mg y -1 of soil Hg, bound to particulate and dissolved organic matter, to the Arctic Ocean (Fisher et al, 2012;Dastoor et al, 2014;Zhang et al, 2015;Sonke et al, 2018). Together with coastal erosion of soils (30 Mg y -1 ), river Hg inputs constitute a terrestrial Hg flux of 74 Mg y -1 to the Arctic Ocean that is of similar magnitude to gross atmospheric deposition over the Arctic Ocean (80 Mg y -1 , Sonke et al, 2018). Permafrost thawing has been shown to enhance river Hg export from soils to rivers https://doi.org/10.5194/bg-2019-483 Preprint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation